Acute exercise-induced glycocalyx shedding does not differ between exercise modalities, but is associated with total antioxidative capacity. Issue 7 (July 2021) - Kröpfl, Julia M.; Beltrami, Fernando G.; Rehm, Markus; Gruber, Hans-Jürgen; Stelzer, Ingeborg; Spengler, Christina M.
Graphical abstract: Abstract: Objectives: Regular physical exercise is known to protect endothelial integrity. It has been proposed that acute exercise-induced changes of the (anti-)oxidative system influence early (glycocalyx shedding) and sustained endothelial activation (shedding of endothelial cells, ECs) as well as endothelial-cell repair by circulating hematopoietic stem and progenitor cells (HPCs). However, results are not conclusive and data in trained participants performing different exercise modalities is lacking. Design: Eighteen healthy, well-trained participants (9 runners, 9 cyclists; age: 29.7 ± 4.2 yrs) performed a strenuous acute exercise session consisting of 4 bouts of 4-min high-intensity with decreasing power profile and 3-min low-intensity in-between. Methods: Average power/speed of intense phases was 85% of the peak achieved in a previous incremental test. Before and shortly after exercise, total oxidative and antioxidative capacities (TAC), shedding of syndecan-1, heparan sulfate, hyaluronan, ECs, and circulating HPCs were investigated. Results: TAC decreased from 1.81 ± 0.42 nmol/L to 1.47 ± 0.23 nmol/L post-exercise (p = 0.010) only in runners. Exercise-induced early and sustained endothelial activation were enhanced post-exercise- syndecan-1: 103.2 ± 63.3 ng/mL to 111.3 ± 71.3 ng/mL, heparan sulfate: from 2637.9 ± 800.1 ng/mL to 3197.1 ± 1416.3 ng/mL, both p < 0.05; hyaluronan: 84.3 ± 21.8 ng/mL to 121.4 ± 29.4 ng/mL, ECs: from 6.6 ± 4.5 cells/μL to 9.5 ± 6.2 cells/μL, both p < 0.01; results were not different between exercise modalities and negatively related to TAC concentrations post-exercise. HPC proportions and self-renewal ability were negatively, while EC concentrations were positively associated with circulating hyaluronan concentrations. Conclusions: These results highlight the importance of the antioxidative system to prevent the endothelium from acute exercise-induced vascular injury – independent of exercise modality – in well-trained participants. Endothelial-cell repair is associated with hyluronan signaling, possibly a similar mechanism as in wound repair.